The theory of the numerical-analytic method: Achievements and new trends of development. I - Ronto, M. I.; Samoilenko, A. M.; Trofimchuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We describe the history of the development of the numerical-analytic method suggested by Samoilenko in 1965 and analyze the relation of this method to other investigations.